2006
DOI: 10.1016/j.jacc.2005.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Expression of Placental Growth Factor Predicts the Improvement of Chronic Phase Left Ventricular Function in Patients With Acute Myocardial Infarction

Abstract: Placental growth factor is rapidly produced in infarct myocardium, especially by endothelial cells during the acute phase of myocardial infarction. Placental growth factor might be over-expressed to compensate the acute ischemic damage, and appears to then act to improve LVEF during the chronic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 41 publications
5
59
2
Order By: Relevance
“…Correlation studies in patients and mouse models indicate that cardiac expression of PlGF promotes wound healing after AMI, possibly by inducing mobilization of mononuclear cells and enhancing angiogenesis (Iwama et al 2006). These data warrant further investigation of whether PlGF therapy may represent a valuable adjunct or alternative to current revascularization strategies for patients with ischemic heart disease.…”
Section: Plgf a Disease-modifying Candidatementioning
confidence: 88%
“…Correlation studies in patients and mouse models indicate that cardiac expression of PlGF promotes wound healing after AMI, possibly by inducing mobilization of mononuclear cells and enhancing angiogenesis (Iwama et al 2006). These data warrant further investigation of whether PlGF therapy may represent a valuable adjunct or alternative to current revascularization strategies for patients with ischemic heart disease.…”
Section: Plgf a Disease-modifying Candidatementioning
confidence: 88%
“…11) In patients with chest pain and acute coronary syndrome, higher PlGF levels have been observed in those with MI and are associated with an increased risk of short-and long-term adverse outcomes. [12][13][14] There are conflicting results regarding circulating sFlt-1 levels in patients with CAD, with some studies noting higher levels during acute MI compared with control pa-tients, 15) and others showing lower plasma sFlt-1 levels in patients during the acute phase of MI compared with control subjects. 16,17) Although PlGF and sFlt-1 might be important biomarkers of chronic heart failure, neither factor has been fully studied in patients with heart failure.…”
mentioning
confidence: 99%
“…We have recently demonstrated that PlGF is produced rapidly in infarcted myocardial tissue, and that the plasma level of PlGF after MI is positively correlated with the improvement in left ventricular function in patients with AMI. 13 These findings suggest that PlGF is involved in post-AMI pathology, infiltration of inflammatory cells, neoangiogenesis, and the development of fibrosis and thus the healing process after AMI. However, therapeutic effects of PlGF administration have not been studied, so in the present study we investigated the result of exogenous administration of PLGF protein in regard to cardiac function and prognosis after MI.…”
mentioning
confidence: 89%
“…The next day, coronary ligation was performed in the same mouse, as previously reported. 13,16 rhPlGF was infused for 3 days and rhsFlt-1 was infused for 7 days. In total, 95 mice were used for assessing survival rate and 74 mice for histological, physiological and biochemical analyses.…”
Section: Preparation Of Mouse Model Of MImentioning
confidence: 99%
See 1 more Smart Citation